PENGEMBANGAN BUKU SAKU EKONOMI BERBASIS ANDROID TERINTEGRASI NILAI ISLAM PADA MATERI BADAN USAHA DALAM PEREKONOMIAN INDONESIA DI SMA NEGERI 1 METRO - Wiwit Kurniawan; Meyta Pritandhari (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The media has an important role in the learning process. But there are some students who do not have learning media. The purpose of this research is to produce an integrated android-based economic handbook of Islamic values on business entity material in a valid and practical class X Indonesian economy. The pocket book was developed in accordance with the systematic and standard criteria for the feasibility of learning media. The research conducted is a type of development research with the 4D development model (Define, Design, Development, Disseminate). The process for producing pocket books begins with the validation stage by media experts, material experts and Islamic religious experts. The pocket book was also trialled at school to measure the response of grade X students in SMA Negeri 1 Metro. The results showed that this pocket book is suitable for use in learning. This is indicated by the results of the validation of media experts with a percentage of 91.2% with very strong criteria, the results of the assessment by material experts with a percentage of 80% with strong criteria, the results of the assessment by Islamic religious experts with a percentage of 96.6% with very strong criteria and the results of testing with a small group of 36 students with a percentage of 90% with very strong criteria. Based on the percentage obtained from the average expert validation of 89.26% with very strong criteria and students' responses of 90% with very strong criteria, the pocket book is declared valid and practical to be used as a reference in the learning process.Keywords: Pocket Book, Learning Media, Android